URGENSI ORGANISASI DAN MANAJEMEN DALAM PEMERINTAHAN - Kanz Yafi Muhammad; Fanila Kasmita Kusuma (Media Bina Ilmiah, 2023)
Government organizations are also stated as wheels of government that come from the community as the source of their legitimacy. Public trust in government must be balanced with good quality performance so that people feel they are getting effective and efficient services. It is known that government management is currently experiencing many problems, both internal and external, that have not been resolved. This study uses a descriptive qualitative approach. The organization and management of the current Indonesian government is heavily influenced by the role of technology. However, the uneven application of ICT, organizational culture that is not the same, leadership that is not yet stable, and the level of ability of human resources that is less reliable means that government organizations have not fully achieved good governance. Policies issued by government organizations in the field of application and use of technology are currently not fully implemented. Every organization has a government service portal but this cannot support a better direction because the use of ICT is still very minimal